Edukasi Penyakit Degeneratif dan Pemeriksaan Kesehatan Pada Masyarakat Di Kelurahan Kayumalue Ngapa Kecamatan Palu Utara - Amsal; Mustafa (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service was carried out in Kayumalue Ngapa Village, North Palu District, focusing on education and early detection of degenerative diseases, such as hypertension, diabetes mellitus, and other metabolic disorders. The main problem in this area is the low level of public awareness of healthy lifestyles and the lack of regular health check-ups, which leads to a high risk of degenerative diseases. The activities included health education and blood pressure, blood sugar, cholesterol, and uric acid screenings for local residents. A total of 20 participants took part in the programme, which also included pre- and post-tests to measure knowledge improvement. The results showed an average score increase from 3.9 to 7.9, indicating the success of the educational intervention. Health screenings revealed that most participants had high risk factors for degenerative diseases, although they had not yet shown severe clinical symptoms. These findings underscore the importance of early detection and community-based preventive interventions. This activity successfully improved community health knowledge and awareness and demonstrated that a participatory, educational, and evidence-based approach is an effective strategy for reducing the risk of degenerative diseases in the community. This programme is recommended for integration into routine primary health care activities and expansion to other areas with similar issues.